Early sedation with Dexmedetomidine in post-operative adult intensive care unit patients: A systematic review. - Mooney, Mary; Corry, Margarita (My University, 2023)
Background Delirium is a leading healthcare concern in adult Intensive Care Units (ICU) and has a reported prevalence of up to 80%. Although individual studies report that early sedation with dexmedetomidine in post-operative patients including its nocturnal administration can improve sleep quality and reduction in ICU delirium, these have not been synthesised in a systematic review. Aim The aim of this systematic review was to evaluate the effectiveness of early administration of dexmedetomidine infusion in the prevention of delirium, reduction in agitation, and improved sleep quality among post-operative adults in ICU. Methods A systematic search was conducted across PubMed, CINAHL, MEDLINE, and EMBASE, together with a search for grey literature. Two authors independently screened the search results, extracted data, and assessed risk of bias. Data were meta-analysed using RevMan 5.4 software. A simplified Cochrane approach was used in this review. Results Five randomised controlled trials with 2173 participants were included. Risk of bias was assessed with the five studies included in this review. Of the five included studies, two were identified as having components with a high risk of bias; one study reporting high risk of bias in the domain of other biases, and the other study in the domains of allocation concealment as well as in the domains of blinding of participants and personnel. All other studies and domains were either low or unclear risk of bias. The result indicated that the incidence of delirium was reduced among the dexmedetomidine group (RR: 0.08, 95% CI -0.15 to -0.01, 3 studies, 1045 patients) when compared to those who received other medications. There was no difference in agitation (RR: 0.85, 95% CI 0.51 to 1.44, 2 studies, 779 patients), and although better sleep was associated with the dexmedetomidine group, no data focusing on the sleep quality was reported. Conclusion The pooled result of this systematic review indicated a reduction in the incidence of delirium among ventilated patients who received early administration of dexmedetomidine post-operatively. Although pooled sample sizes are relatively high, each outcome is based on one or two studies of primarily low or unclear risk of bias. Further research is warranted to determine the potential benefit of dexmedetomidine on agitation and sleep quality.
PUBLISHED
http://doi.org/10.1111/nicc.12912
Keywords: intensive care, Critical care, delirium